PENGARUH MEDIA DIGITAL MATH CENTER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 1 SDN 2 SELOGENDER - Lusiana; Novia Rahma Rista Utami; Uci Ulfa Nur’afifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Digital Math Center Media on the mathematics learning outcomes of first-grade students at SDN 2 Selogender. The research employed a quantitative method with a quasi-experimental design using a Non-Equivalent Control Group Design. The sample consisted of 40 students, including 20 students in the experimental group and 20 students in the control group. Data were collected using pretest and posttest instruments and analyzed through validity, reliability, normality, homogeneity tests, and the Independent Sample t-Test. The results showed that the average learning outcome of the experimental group was 87.70, which was higher than the control group’s average of 73.00, with a significance value of 0.000 < 0.05. It can be concluded that the Digital Math Center Media has a significant and effective impact on improving the mathematics learning outcomes of first-grade students at SDN 2 Selogender.